The Influence of Productive Zakat Through Z-Chicken Program on The Income Level of Mustahik - Salma, Anisah Salma Ramadhani; Rizqon, Abdul Latif; Fajri, Mohammad Zen Nasrudin; Sholihah, Fefi Diniyati; Julian, Antoni (Universitas Darussalam Gontor, 2025)
This study aims to determine the effect of the Z-chicken program on mustahik income levels at BAZNAS Bojonegoro Regency. With this program, it is hoped that mustahik can run their business continuously so that they can become muzakki. The research method used is quantitative research using simple linear regression method. The sample in this study amounted to 30 respondents. Data collection using a questionnaire through google form and data processing using SPSS version 26.0 analysis tools. The results showed that the Z-Chicken program provided by Baznas Bojonegoro had an influence of 81.6% on the income level of mustahik, while the rest was influenced by other factors not included in this study, which was 18.4%. In the t test results, the Z-Chicken program has a significant positive effect on mustahik income levels. The calculated t value of 11.136 is greater than the t table value of 1.701, which means that the hypothesis is accepted, that is, the Z-Chicken program has a positive and significant effect on the income level of mustahik.